2014
DOI: 10.1155/2014/789450
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Patients Requiring Intensive Care: A One Year Retrospective Study in a Tertiary Care Institute in India

Abstract: Background and Objectives. Critically ill obstetric patients are a particularly unique cohort for the intensivist. The objective of this study was to review the indications for admission, demographics, clinical characteristics, and outcomes of obstetric patients admitted to intensive care unit of a medical college hospital in southern India and to identify conditions associated with maternal mortality. Design. Retrospective analysis of pregnant/postpartum (up to 6 weeks) admissions over a 1-year result. We st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
53
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 4 publications
10
53
3
Order By: Relevance
“…The commonest surgical procedure performed was the emergency cesarean section (37.12 %). Other studies report a high percentage of cesarean sections among ICU patients, 78.5 % [10], 50.7 % [4], 52.9 % [5], and 67.27 % [20], compared to this study. This indicates that most of the women needed operative delivery.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The commonest surgical procedure performed was the emergency cesarean section (37.12 %). Other studies report a high percentage of cesarean sections among ICU patients, 78.5 % [10], 50.7 % [4], 52.9 % [5], and 67.27 % [20], compared to this study. This indicates that most of the women needed operative delivery.…”
Section: Discussioncontrasting
confidence: 52%
“…Studies done so far report postpartum admissions as the majority. Some studies have reported a majority of antepartum admissions [13,20], and delivery admissions (on the day of delivery) [6,21], some studies have reported a high rate, though not the majority [10,15]. Epidemiology of antepartum admissions needs further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the report from Australia, Ashraf et al, [11] in a retrospective review of ICU admissions in a teaching hospital in India, showed that obstetric haemorrhage and hypertensive disorders were the most common reasons for ICU admission of obstetric patients. Eighty-five per cent of the patients required mechanical ventilation and 78% required inotropic support.…”
mentioning
confidence: 69%
“…Very few studies have been conducted in India evaluating the reason for ICU admissions of critically ill obstetric patients in tertiary hospitals across India. [10][11][12] The present study was conducted to evaluate the indications for admission, course and outcome of the critically ill obstetric patients in Kashmir valley, in order to evaluate the patient characteristics of critically ill obstetric patients so that high risk obstetric patients are identified early and managed appropriately with early involvement of multidisciplinary obstetric intensive care team.…”
Section: Introduction:-mentioning
confidence: 99%